Patient readiness for hospital discharge and its relationship to discharge preparation and structural factors: A cross-sectional study - Mabire, Cedric; Bachnick, Stefanie; Ausserhofer, Dietmar; Simon, Michael (International journal of nursing studies)
Nursing discharge preparation is vital to successful hospital-to-home transitions. However, despite a wealth of evidence on its effectiveness, little is known of the structure- and process-related factors that facilitate or impede its use in clinical practice. Specifically, the associations between unit size and type, leadership support, skill mix, staffing, nurse and patient characteristics, discharge teaching and patient readiness for discharge have rarely been studied. This study aimed to explore the associations between structure-individual characteristics (i.e., unit, nurse and patient characteristics) and process-related (i.e., teaching of self-care and symptom management) factors and patient readiness for hospital discharge. A secondary data analysis of the multicentre observational “Matching Registered Nurse services with changing care demands (MatchRN)” study. Data were collected between September 2015 and January 2016 on 123 surgical, medical and mixed units in 23 Swiss acute care hospitals. A total of 1833 registered nurses and 1755 patients were included in the analyses. Structure-, process- and patient readiness-related hospital discharge variables were assessed using validated items either from existing instruments or self-developed. Multilevel mixed-effects logistic regression was used to test associations. Fewer than half of the patients hospitalized (47.8%) reported readiness for hospital discharge. Fifty-eight percent reported receiving discharge preparation interventions for self-care and 30% for symptom management. Patients’ readiness for hospital discharge was significantly lower in larger units (β = −0.001; 95% confidence interval (CI) = −0.002 to −0.001) and on medical units (β = −0.44; 95% CI = −0.70 to −0.19). Higher nurses’ experience (β = .004; 95% CI = 0.001 to 0.01), better patient self−reported health (β = −0.11; 95% CI = −0.17 to −0.05), higher patient ratings of self-care teaching (β = 1.33; 95% CI = 1.07–1.59) and symptom management teaching (β = 0.79; 95% CI = 0.52–1.06) were significantly associated with greater patient readiness for hospital discharge. Patient readiness for hospital discharge is associated with process- and structure-related factors. Our findings suggest that, for successful uptake in clinical practice, the development and implementation of effective discharge preparation programs should consider the structural context, i.e., patient population, unit size, and experience of nurses within the team. Furthe